Evaluasi Kinerja RSUD Raja Ahmad Tabib Provinsi Kepulauan Riau dalam Meningkatkan Kualitas Layanan Publik - Agra Dinda Nodori; Baiq Riska Nabila Anggraini Putri; Yesi Valentine (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This article is an evaluation of the performance of Raja Ahmad Tabib Hospital of Riau Islands Province in improving the quality of public services. The evaluation was conducted through malpractice cases, surgical services, and community satisfaction index surveys. The research method used is Literature Review, Literature Review is a systematic, clear, and repetitive method for identifying, evaluating, and synthesising scientific research and ideas. The evaluation results show that this hospital has achieved some performance indicators, but there are still some indicators that have not been achieved. The submission of the Raja Ahmad Tabib Hospital's performance report aims to realise the hospital's accountability to the mandate giver. The performance evaluation of RAT RSUD shows the existence of special and general surgical services, as well as efforts to fulfil specialist doctors. However, there was a case of alleged malpractice at this hospital, which was denied by the hospital. Malpractice is a bad medical act committed by a doctor against a patient, and can have legal implications for the hospital, doctor, and patient. Performance evaluation and government agency performance reports (LKIP) are also an important part of hospital accountability.